Super-slippery double-network hydrogel based on inhibition effect and preparation method and application thereof
By using a mold with oxygen isolation function and performing ultraviolet irradiation during the preparation of the hydrogel, combined with the method of introducing trivalent iron ions into the second layer of network hydrogel, the existing hydrogel has a high friction coefficient. Problem, a significant reduction in friction coefficient and a long-term lubrication performance are achieved.
Patent Information
- Application Number
- CN202410327126.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-03-21
AI Technical Summary
The friction coefficient of existing hydrogels is still higher than that of natural articular cartilage, and the friction experiment time is short, making it difficult to meet the lubricating performance requirements for practical applications.
Using a mold that has at least partial isolation effect on oxygen and performs two ultraviolet irradiation, the friction coefficient of the hydrogel is reduced by the inhibitory effect of oxygen, and the inhibitor trivalent iron ions are introduced into the second layer of network hydrogel to enhance inhibition. effect.
The friction coefficient of the hydrogel is significantly reduced, making it reaching a minimum of 0.00383, and maintains the optimal lubricating characteristics after 6 hours of continuous friction.
Smart Images

Figure CN118185070B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to an ultra-slippery double-network hydrogel based on an inhibitory effect, and a preparation method and application thereof. Background Art
[0002] Hydrogels are soft materials composed of cross-linked polymer networks containing a large amount of water. They are widely used in biomedicine, soft robotics, agriculture and other fields. When hydrogels move against the surfaces of other materials, excellent lubrication is crucial. This lubrication property has unique advantages in some fields, the most typical of which is artificial articular cartilage. With the aging of the population and the increase in obesity rates, osteoarthritis has become an increasingly serious global health problem. Artificial joint replacements for the treatment of severe arthritis are becoming more frequent. Therefore, hydrogels have become more important as excellent candidate materials for artificial articular cartilage. In practical applications, lubrication properties have become one of the core features of hydrogels.
[0003] At present, a variety of methods have been developed to improve the lubrication properties of hydrogels, such as reducing the friction coefficient based on the boundary layer formed by liposomes (CN115569235B, a method for preparing a hydrogel based on lipid lubrication); using functional molecules with lubricating properties to form a lubricating layer to achieve long-lasting lubrication (CN116854940A, a long-lasting lubricating hydrogel and its preparation method). These methods reduce the friction coefficient of hydrogels, but the absolute value of the friction coefficient of hydrogels is still far behind that of natural articular cartilage, and the friction test time is very short.
[0004] Therefore, how to effectively reduce the friction coefficient of hydrogel is of great significance to improving the lubrication performance of hydrogel. Summary of the invention
[0005] In view of this, the present application aims to provide a method for preparing a super-slippery double-network hydrogel based on an inhibitory effect. During the preparation process of the hydrogel, a mold that has at least partial isolation from oxygen is used and two ultraviolet irradiations are performed. The inhibitory effect of oxygen can be used to reduce the friction coefficient of the hydrogel and improve the lubrication properties of the hydrogel.
[0006] Another object of the present application is to provide a super-slippery double-network hydrogel based on the inhibitory effect.
[0007] Another object of the present application is to provide an application of super-slippery double-network hydrogel based on the inhibitory effect.
[0008] To achieve the above objectives, the first aspect of the present application proposes a method for preparing a super-slippery double-network hydrogel based on an inhibitory effect, comprising:
[0009] subjecting the first precursor solution to a first ultraviolet irradiation in a first mold to obtain a first layer of network hydrogel;
[0010] Performing a first swelling of the first layer of network hydrogel in a second precursor solution to obtain an intermediate;
[0011] The intermediate is subjected to a second ultraviolet irradiation in a second mold to obtain a second layer of network hydrogel;
[0012] The first mold and the second mold are molds that have a function of at least partially isolating oxygen.
[0013] In some embodiments, the material of the first mold and the second mold includes at least one of glass, polymethyl methacrylate, polystyrene, and polycarbonate.
[0014] In some embodiments, the first precursor solution includes a first monomer, a first cross-linking agent, and a first photoinitiator.
[0015] In some embodiments, the second precursor solution includes a second monomer, a second cross-linking agent, and a second photoinitiator.
[0016] In some embodiments, the first mold is made of a material that completely isolates oxygen, and the second mold is made of a material that allows oxygen to pass through.
[0017] Preferably, the first mold is made of glass, and the second mold is made of polymethyl methacrylate.
[0018] In some embodiments, the first monomer includes at least one of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, methacrylamide, sodium acrylate, and 2-hydroxyethyl methacrylate.
[0019] In some embodiments, the first cross-linking agent and the second cross-linking agent both include at least one of N,N′-methylenebisacrylamide and ethylene glycol dimethacrylate.
[0020] In some embodiments, the first photoinitiator and the second photoinitiator both include at least one of phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt and photoinitiator 2959.
[0021] In some embodiments, the mass ratio of the first monomer, the first cross-linking agent, and the first photoinitiator is (15-22): (0.1-1): (0.01-0.03).
[0022] In some embodiments, the second monomer includes at least one of acrylic acid and methacrylic acid.
[0023] In some embodiments, the mass ratio of the second monomer, the second cross-linking agent, and the second photoinitiator is (10-14): (0.05-0.2): (0.01-0.03).
[0024] In some embodiments, the first mold is made of a material that completely isolates oxygen, and the second mold is made of a material that at least partially isolates oxygen.
[0025] In some embodiments, the first mold and the second mold are both made of glass.
[0026] In some embodiments, the second precursor solution or the second precursor solution and the first precursor solution contain trivalent iron ions.
[0027] In some embodiments, the concentration of the trivalent iron ions in the second precursor solution or the second precursor solution and the first precursor solution is 0.001-0.9 mmol / L.
[0028] In some embodiments, in the first ultraviolet irradiation and the second ultraviolet irradiation, the wavelength of the ultraviolet rays is 350-370 nm, and the time of the ultraviolet irradiation is 1-5 h.
[0029] In some embodiments, the method for preparing the ultra-slippery double-network hydrogel based on the inhibitory effect further includes a step of subjecting the intermediate product obtained after the second ultraviolet irradiation to a second swelling step in pure water.
[0030] In some embodiments, the first swelling time is 40-56 hours.
[0031] In some embodiments, the second swelling time is 40-56 hours.
[0032] In some embodiments, during the second swelling process of the intermediate product obtained after the second ultraviolet irradiation in pure water, the pure water is replaced every 10-12 hours.
[0033] The second aspect of the present application proposes a super-slippery double network hydrogel based on an inhibitory effect, which is prepared using the preparation method of the super-slippery double network hydrogel based on an inhibitory effect described in the present application.
[0034] In some embodiments, the super-slippery double-network hydrogel based on the inhibitory effect includes the first layer of network hydrogel and the second layer of network hydrogel, and the second network hydrogel is coated on at least a portion of the outer layer of the first layer of network hydrogel.
[0035] In some embodiments, the friction coefficient of the super-slippery double network hydrogel based on the inhibition effect is 0.00383-0.01.
[0036] The third aspect of the present application relates to the application of the super-slippery double-network hydrogel based on the inhibitory effect described in the present application in the fields of cartilage repair, soft robotics, and medical device surface lubrication.
[0037] The method for preparing the super-slippery double-network hydrogel based on the inhibitory effect described in the present application can at least bring the following beneficial effects:
[0038] 1. In the process of preparing the hydrogel, a mold that has at least partial isolation from oxygen is used and ultraviolet irradiation is performed twice. The inhibitory effect of oxygen can reduce the friction coefficient of the hydrogel and improve the lubrication performance of the hydrogel.
[0039] 2. Introducing the inhibitor trivalent iron ions into the second hydrogel to make it participate in the polymerization reaction of the hydrogel and act on the free radicals generated by the second initiator. At the same time, using the first mold with oxygen isolation function and the second mold with at least partial oxygen isolation function can achieve a better inhibition effect, thereby significantly reducing the friction coefficient of the hydrogel to a minimum of 0.00383. Even after 6 hours of continuous friction, the friction coefficient of the hydrogel is still maintained at 0.0072.
[0040] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings.
[0042] in:
[0043] Figure 1 A schematic diagram of the synthesis of a method for preparing a super-slippery double-network hydrogel based on an inhibitory effect, shown as an exemplary embodiment of the present application.
[0044] Figure 2 A schematic synthesis diagram of a method for preparing a super-slippery double-network hydrogel based on an inhibitory effect, shown as another exemplary embodiment of the present application.
[0045] Figure 3 This is a schematic diagram of the first mold and the second mold in an exemplary embodiment of the present application, wherein: a is a design framework diagram, b is a physical diagram before combination, c is a schematic diagram after combination, and d is a schematic diagram of purple dye.
[0046] Figure 4Graph showing the influence of oxygen inhibition effect on the friction coefficient of hydrogel, wherein Glass-PMMA-Gel, Glass-Glass-Gel, PMMA-PMMA-Gel, and PMMA-Glass-Gel represent the hydrogels prepared in Example 8, Example 1, Example 9, and Example 10, respectively.
[0047] Figure 5 A comparison of the inhibition of hydrogel polymerization by different concentrations of trivalent iron ions.
[0048] Figure 6 : is the effect of trivalent iron ion concentration on the friction coefficient (i.e., the friction coefficient comparison diagram of the hydrogels prepared in Examples 1-7), where 0 mM Fe 3+ , 0.15mM Fe 3+ , 0.3 mM Fe 3+ , 0.45mM Fe 3+ , 0.6 mM Fe 3+ , 0.75 mM Fe 3 + , 0.9 mM Fe 3+ They represent the hydrogels prepared in Example 1, Example 2, Example 3, Example 4, Example 5, Example 6 and Example 7 respectively.
[0049] Figure 7 Figure 2 is the effect of load and friction time on the friction performance of hydrogels, where PMMA-Glass-Gel represents the hydrogel prepared in Example 10, Glass-PMMA-Gel represents the hydrogel prepared in Example 8, DN-Hydrogel-0.3Fe 3+ The hydrogel prepared in Example 3 is represented by the left figure a showing the effect of load change on the friction performance of the hydrogel, and the right figure b showing the effect of friction time change on the friction performance of the hydrogel.
[0050] Figure 8 : is a trend diagram of the change of friction coefficient with speed, wherein: Glass-Gel represents the hydrogel prepared in Comparative Example 1, and PMMA-Gel represents the hydrogel prepared in Comparative Example 2. DETAILED DESCRIPTION
[0051] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.
[0052] In this application, the disclosure of numerical ranges includes all values within the entire range and the disclosure of further subdivided ranges, including the endpoints and sub-ranges given in these ranges.
[0053] In this application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.
[0054] The inventors found that although the prior art methods for improving the lubrication properties of hydrogels reduced the friction coefficient of hydrogels, the absolute value of the friction coefficient of hydrogels was still far behind that of natural articular cartilage, and the friction test time was very short. In order to solve this problem, the inventors improved the lubrication properties of hydrogels based on the inhibitory effect (strategy) in double-network hydrogels (the mechanical properties of double-network hydrogels are closer to practical applications). The friction coefficient of the hydrogel was greatly reduced, the minimum friction coefficient was also very low, and after 6 hours of long-term continuous friction, it still maintained excellent lubrication properties, which is very beneficial for practical applications. Specifically, the idea of reducing the friction coefficient of hydrogels based on the inhibitory effect in this application is: ultra-slippery double-network hydrogels are synthesized by using oxygen in the air and trivalent iron ions, a high-efficiency inhibitor, to achieve the inhibitory effect. The first is to use oxygen in the air ( Figure 1 ), this method uses the first mold and the second mold to synthesize the double network hydrogel, so when the permeability of the first mold and the second mold to gas changes, the oxygen permeation during the hydrogel polymerization process can be adjusted. In the inhibition effect of oxygen, it is found that the inhibition effect only acts on the second layer of network hydrogel to achieve the best friction performance. Based on this experimental conclusion, the introduction of high-efficiency inhibitor trivalent iron ions further explores the potential of the inhibition effect to reduce the friction coefficient.
[0055] The following describes a method for preparing a super-slippery double-network hydrogel based on an inhibitory effect according to an embodiment of the present application with reference to the accompanying drawings.
[0056] Figure 1 A schematic diagram of the synthesis of a method for preparing a super-slippery double-network hydrogel based on an inhibitory effect, shown as an exemplary embodiment of the present application.
[0057] like Figure 1 As shown, the method for preparing the super-slippery double-network hydrogel based on the inhibitory effect of the embodiment of the present application comprises the following steps:
[0058] S101, subjecting a first precursor solution to a first ultraviolet irradiation in a first mold to obtain a first layer of network hydrogel.
[0059] In the embodiment of the present application, in step S101, the purpose of the first ultraviolet irradiation is to use ultraviolet light to make the photoinitiator generate free radicals, thereby forming free radical polymerization, and polymerizing the monomers into high molecular polymers.
[0060] In some embodiments, the first precursor solution includes a first monomer, a first cross-linking agent, and a first photoinitiator.
[0061] In some embodiments, the mass ratio of the first monomer, the first cross-linking agent, and the first photoinitiator is (15-22): (0.1-1): (0.01-0.03), for example, 18.2: 0.6: 0.02.
[0062] It should be noted that, as an optional example, in the first precursor solution, except for the first monomer, the first cross-linking agent, and the first photoinitiator, the remainder is water, wherein the water may be, for example, ultrapure water, distilled water, or the like.
[0063] In some embodiments, the first monomer includes, but is not limited to, at least one of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, methacrylamide, sodium acrylate, 2-hydroxyethyl methacrylate, and the like.
[0064] As an optional example, the first monomer consists of acrylamide (AAm) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS).
[0065] As a non-limiting example, when the first monomer consists of acrylamide (AAm) and 2-acrylamide-2-methylpropane sulfonic acid (AMPS), the mass ratio of acrylamide (AAm) to 2-acrylamide-2-methylpropane sulfonic acid (AMPS) is (0.8-1.6):(12-22), including but not limited to 0.8:12, 0.8:22, 1.6:12, 1.6:22 or 1,2:1.7, etc.
[0066] In some embodiments, the mass fraction of the first monomer in the first precursor solution is 15-22%, including but not limited to 15%, 17%, 19% or 22%.
[0067] In some embodiments, the first cross-linking agent includes, but is not limited to, at least one of N,N′-methylenebisacrylamide, ethylene glycol dimethacrylate, and the like.
[0068] In some embodiments, the mass fraction of the first cross-linking agent in the first precursor solution is 0.1-1%, including but not limited to 0.1%, 0.25%, 0.6%, 0.75% or 1%, etc.
[0069] As an optional example, the first cross-linking agent is N,N'-methylenebisacrylamide (MBAA), and the mass fraction of the first cross-linking agent in the first precursor solution is 0.1%.
[0070] In some embodiments, the first photoinitiator includes at least one of lithium phenyl (2,4,6-trimethylbenzoyl) phosphate (LAP) and photoinitiator 2959.
[0071] In some embodiments, the mass fraction of the first photoinitiator in the first precursor solution is 0.01-0.03%, including but not limited to 0.01%, 0.015%, 0.02%, 0.025% or 0.03%, etc.
[0072] As an optional example, the first photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, and the mass fraction of the first photoinitiator in the first precursor solution is 0.02%.
[0073] In some embodiments, the first mold is a mold having a function of at least partially isolating oxygen.
[0074] It can be understood that the first mold can be a mold with a function of completely isolating oxygen, or a mold with a function of partially isolating oxygen (that is, at least partially allowing oxygen to pass through).
[0075] It should be noted that, in the embodiments of the present application, the mold having the function of at least partially isolating oxygen can be achieved through the structure of the mold, and can also be achieved by selecting the material of the mold.
[0076] In some embodiments, the material of the first mold is at least one of glass, polymethyl methacrylate (PMMA), polystyrene, polycarbonate, etc.
[0077] When the material is glass, since glass is a dense inorganic substance and can isolate oxygen very well, the first mold has the function of completely isolating oxygen.
[0078] When the material is polymethyl methacrylate (PMMA), PMMA is an organic substance composed of polymer chains, and oxygen can pass through PMMA relatively easily, inhibiting free radicals generated during the polymerization process and exerting an inhibitory effect. Therefore, at this time, the first mold has the function of partially isolating oxygen (that is, at least partially allowing oxygen to pass through).
[0079] In some embodiments, in the first ultraviolet irradiation, the wavelength of ultraviolet rays is 350-370nm, including but not limited to 350nm, 355nm, 360nm, 365nm or 370nm.
[0080] In some embodiments, in the first ultraviolet irradiation, the ultraviolet irradiation time is 1-5 hours, including but not limited to 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.
[0081] S102, subjecting the first layer of network hydrogel obtained in step S101 to a first swelling in a second precursor solution to obtain an intermediate.
[0082] In some embodiments, the first layer of network hydrogel obtained in step S102 is swollen in the second precursor solution, with the purpose of allowing the monomers, crosslinking agents and initiators in the second precursor solution to penetrate into the first layer of network hydrogel.
[0083] In some embodiments, the second precursor solution includes a second monomer, a second cross-linking agent, and a second photoinitiator.
[0084] In some embodiments, the mass ratio of the second monomer, the second cross-linking agent, and the second photoinitiator is (10-14): (0.05-0.2): (0.01-0.03), for example, 12: 0.1: 0.02.
[0085] It should be noted that, as an optional example, in the second precursor solution, except for the second monomer, the second cross-linking agent, and the second photoinitiator, the rest is water, wherein the water may be, for example, ultrapure water, distilled water, or the like.
[0086] In the embodiments of the present application, the second monomer needs to meet two restrictions: 1. It can form a flexible polymer chain through free radical polymerization; 2. The second precursor solution needs to be acidic, otherwise the trivalent iron is easily hydrolyzed to form a colloid. Therefore, in some cases, the second monomer is acidic, such as acrylic acid, methacrylic acid, etc.; in other cases, the second monomer is a non-acidic monomer, and additional acid needs to be added to avoid hydrolysis of the trivalent iron.
[0087] As an optional example, the second monomer includes but is not limited to at least one of acrylic acid (AAc), methacrylic acid, and the like.
[0088] In some embodiments, the mass fraction of the second monomer in the second precursor solution is 10-14%, including but not limited to 10%, 11%, 12%, 13% or 14%, etc.
[0089] As an optional example, the second monomer is acrylic acid, and the mass fraction of the second monomer in the second precursor solution is 0.1%.
[0090] In some embodiments, the second cross-linking agent includes, but is not limited to, at least one of N,N′-methylenebisacrylamide (MBAA), ethylene glycol dimethacrylate, and the like.
[0091] In some embodiments, the mass fraction of the second cross-linking agent in the second precursor solution is 0.05-0.2%, including but not limited to 0.05%, 0.1%, 0.15% or 0.2%.
[0092] As an optional example, the second cross-linking agent is N,N'-methylenebisacrylamide, and the mass fraction of the second cross-linking agent in the second precursor solution is 12%.
[0093] In some embodiments, the second photoinitiator includes, but is not limited to, at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP), photoinitiator 2959, and the like.
[0094] In some embodiments, the mass fraction of the second photoinitiator in the second precursor solution is 0.01-0.03%, including but not limited to 0.01%, 0.015%, 0.02%, 0.025% or 0.03%, etc.
[0095] As an optional example, the second photoinitiator is phenyl (2,4,6-trimethylbenzoyl) lithium phosphate, and the mass fraction of the second photoinitiator in the second precursor solution is 0.02%.
[0096] In some embodiments, the first swelling time is 40-56 hours, including but not limited to 40 hours, 44 hours, 48 hours, 52 hours or 56 hours.
[0097] In some embodiments, the first swelling is performed in an air atmosphere.
[0098] In the embodiments of the present application, the purpose of the first swelling is to balance the internal and external osmotic pressures of the hydrogel, and at the same time, the swelling significantly increases the volume of the hydrogel, which is beneficial for the components in the second precursor solution to enter the hydrogel.
[0099] S103, subjecting the intermediate obtained in step S102 to a second ultraviolet irradiation in a second mold to obtain a second layer of network hydrogel (that is, the final super-slippery double network hydrogel based on the inhibition effect).
[0100] In the embodiment of the present application, in step S103, the purpose of the second ultraviolet irradiation is to use ultraviolet light to make the photoinitiator generate free radicals, thereby forming free radical polymerization, and polymerizing the monomers into high molecular polymers.
[0101] In some embodiments, the second mold is a mold having a function of at least partially isolating oxygen.
[0102] It can be understood that the second mold can be a mold with a function of completely isolating oxygen, or can be a mold with a function of partially isolating oxygen (that is, at least partially allowing oxygen to pass through).
[0103] It should be noted that, in the embodiments of the present application, the mold having the function of at least partially isolating oxygen can be achieved through the structure of the mold, and can also be achieved by selecting the material of the mold.
[0104] In some embodiments, the material of the second mold is at least one of glass, polymethyl methacrylate (PMMA), polystyrene, polycarbonate, etc.
[0105] When the material is glass, since glass is a dense inorganic substance and can isolate oxygen very well, the second mold has the function of completely isolating oxygen.
[0106] When the material is polymethyl methacrylate (PMMA), PMMA is an organic substance composed of polymer chains, and oxygen can pass through PMMA relatively easily, inhibiting free radicals generated during the polymerization process and exerting an inhibitory effect. Therefore, at this time, the second mold has the function of partially isolating oxygen (that is, at least partially allowing oxygen to pass through).
[0107] In some embodiments, in the second ultraviolet irradiation, the wavelength of ultraviolet rays is 350-370nm, including but not limited to 350nm, 355nm, 360nm, 365nm or 370nm.
[0108] In some embodiments, in the second ultraviolet irradiation, the ultraviolet irradiation time is 1-5 hours, including but not limited to 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.
[0109] In some embodiments, the method for preparing a super-slippery double-network hydrogel based on the inhibitory effect further includes a step of subjecting the intermediate product obtained after the second ultraviolet irradiation to a second swelling in pure water. The purpose of the second swelling is to remove the unreacted monomers. It should be noted that in the embodiments of the present application, even if there is a small amount of residual first monomer in the hydrogel, this part of the first monomer will still participate in free radical polymerization during the second polymerization (i.e., the second ultraviolet irradiation). Therefore, the monomers removed by the second swelling are mainly the second monomers, as well as possible and trace amounts of the first monomers.
[0110] In some embodiments, the second swelling time is 40-56 hours, including but not limited to 40 hours, 44 hours, 48 hours, 52 hours or 56 hours.
[0111] In some embodiments, the second swelling is performed in an air atmosphere.
[0112] In some embodiments, during the second swelling process of the intermediate product obtained after the second ultraviolet irradiation in pure water, the pure water is replaced every 10-12 hours (eg, 10 hours, 11 hours or 12 hours, etc.) to remove the unreacted monomers.
[0113] In some embodiments, Figure 2As shown, the second precursor solution also contains trivalent iron ions. In the embodiment of the present application, an inhibitor trivalent iron ion is added to the second precursor solution, and the inhibitor trivalent iron ion participates in the polymerization reaction of the second layer of network hydrogel, acts on the free radicals generated by the second initiator, and then can exert an inhibitory effect, so that the friction coefficient is significantly reduced. The inhibitory effect is mainly achieved by reducing the covalent cross-linking of the hydrogel, forming a loose hydrogel network and a large number of polymer catenaries, reducing the shear force during the friction process, and then reducing the friction coefficient of the hydrogel.
[0114] In some embodiments, the ferric iron ions may be derived from a variety of soluble ferric iron salts.
[0115] As a non-limiting example, the soluble ferric salt includes, but is not limited to, at least one of ferric nitrate, ferric chloride, ferric sulfate, and the like.
[0116] It should be noted that in the embodiments of the present application, the anions in the soluble ferric salt do not participate in the reaction, so the salt that can provide ferric ions can exert an inhibitory effect and significantly reduce the friction coefficient. At the same time, since the ferric ions act on the free radicals generated by the second initiator, the concentration of the ferric ions is at the same order of magnitude as the concentration of the second initiator.
[0117] In some embodiments, the concentration of the trivalent iron ions in the second precursor solution is 0.001-0.9 mmol / L. In the embodiments of the present application, the concentration of the trivalent iron ions in the second precursor solution is within the above range, which can reduce the friction coefficient of the hydrogel; if it is lower than 0.001 mmol / L, it may not have a significant effect; if it is higher than 0.9 mmol / L, the friction coefficient of the hydrogel increases.
[0118] It should be noted that when the second precursor solution does not contain trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application only relies on the oxygen inhibition effect to reduce the friction coefficient. At this time, the inventor found that when the material of the first mold is a material with the function of completely isolating oxygen and the material of the second mold is a material that allows oxygen to pass through, the super-slippery double network hydrogel based on the inhibitory effect obtained by the method for preparing the super-slippery double network hydrogel based on the inhibitory effect has the lowest friction coefficient, which shows that only introducing inhibitors such as trivalent iron ions in the second precursor solution can play the best effect of reducing the friction coefficient.
[0119] Therefore, in some embodiments, when the second precursor solution does not contain trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibition effect of the embodiment of the present application only relies on the oxygen inhibition effect to reduce the friction coefficient (such as Figure 1As shown, as a preferred example, the material of the first mold is a material that has the function of completely isolating oxygen, and the material of the second mold is a material that allows oxygen to pass through. As a non-limiting example, the material of the first mold is glass, etc., and the material of the second mold is polymethyl methacrylate (PMMA), etc.
[0120] As an optional example, when the second precursor solution does not contain trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibition effect of the embodiment of the present application only relies on the oxygen inhibition effect to reduce the friction coefficient, such as Figure 1 As shown, the method for preparing the super-slippery double-network hydrogel based on the inhibitory effect of the embodiment of the present application comprises:
[0121] The first precursor solution is poured into the first mold and irradiated for 3 hours under 365nm ultraviolet light. Then the hydrogel after the reaction is taken out from the first mold, placed in the prepared second precursor solution, and swelled for 48 hours. Take out the fully swollen hydrogel, put it into the second mold again, and irradiate for 3 hours under 365nm ultraviolet light. Take out the double network hydrogel after the reaction from the second mold, fully swell in pure water for 48 hours, and replace pure water every 12 hours to remove the unreacted monomer. Wherein, the material of the first mold and the second mold is glass (Glass) or polymethyl methacrylate (PMMA). Preferably, the material of the first mold is glass (Glass), and the material of the second mold is polymethyl methacrylate (PMMA).
[0122] In other embodiments, when the second precursor solution contains trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application relies on the inhibitory effect of inhibitors such as trivalent iron ions or the inhibitory effect of inhibitors such as trivalent iron ions and the oxygen inhibitory effect to reduce the friction coefficient (such as Figure 2 As shown), the material of the first mold is a material that has the function of completely isolating oxygen, and the material of the second mold is a material that has the function of at least partially isolating oxygen.
[0123] As a non-limiting example, when the second precursor solution contains trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application only relies on the inhibitory effect of the trivalent iron ions and other inhibitors to reduce the friction coefficient (such as Figure 2 As shown), in order to avoid interference from oxygen in the air, the material of the first mold and the material of the second mold are both materials that have the function of completely isolating oxygen, such as glass.
[0124] As a non-limiting example, when the second precursor solution contains trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application relies on the inhibitory effect of the inhibitor such as trivalent iron ions and the oxygen inhibitory effect to jointly reduce the friction coefficient (such as Figure 2 As shown), the material of the first mold is a material that has the function of completely isolating oxygen, such as glass; the material of the second mold is a material that allows oxygen to pass through, but the oxygen permeability of the second mold needs to be controlled to be lower than the oxygen permeability of the second mold that simply relies on the oxygen inhibition effect to reduce the friction coefficient, so as to ensure that the inhibitory effect of inhibitors such as trivalent iron ions and the oxygen inhibition effect work synergistically to ensure a better effect of reducing the friction coefficient.
[0125] As an optional example, when the second precursor solution contains trivalent iron ions, the method for preparing the super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application relies on the inhibitory effect of inhibitors such as trivalent iron ions or the inhibitory effect of inhibitors such as trivalent iron ions and the oxygen inhibitory effect to reduce the friction coefficient, such as Figure 2 As shown, the method for preparing the super-slippery double-network hydrogel based on the inhibitory effect of the embodiment of the present application comprises:
[0126] Pour the first precursor solution into the first mold and irradiate it under 365nm ultraviolet light for 3 hours. Then take out the reacted hydrogel from the first mold, put it into the prepared second precursor solution with a trivalent iron ion concentration range of 0.001-0.9mmol / L, and swell it for 48 hours. Take out the fully swollen hydrogel, put it into the second mold again, and irradiate it under 365nm ultraviolet light for 3 hours. Take out the double network hydrogel that has completed the reaction from the second mold, fully swell it in pure water for 48 hours, and replace the pure water every 12 hours to remove the unreacted monomers. The synthesized hydrogel is named DN-Hydrogel-XFe 3+ , where X means that the concentration of trivalent iron ions is X mmol / L. Wherein, the first mold and the second mold are both made of glass.
[0127] It should be noted that the first precursor solution of the present application and the second precursor solution without inhibitors such as trivalent iron ions, in addition to the composition of the present application, can also be other precursor solution compositions well known in the art that are suitable for double network hydrogels.
[0128] It should also be noted that in the embodiments of the present application, the structures of the first mold and the second mold are not limited, and can be any mold known in the art that can be used to make double-network hydrogels, for example, Figure 3 The mold shown.
[0129] In some embodiments, the method for preparing a super-slippery double-network hydrogel based on the inhibition effect of an embodiment of the present application further includes the steps of preparing a first precursor solution and a second precursor solution.
[0130] As a non-limiting example, the method for preparing the first precursor solution includes: dissolving the first monomer in water, and then adding the first cross-linking agent and the first photoinitiator and mixing them.
[0131] As a non-limiting example, when the second precursor solution does not contain trivalent iron ions, the method for preparing the second precursor solution includes: dissolving the second monomer, the second cross-linking agent, and the second photoinitiator in water.
[0132] As a non-limiting example, when the second precursor solution contains trivalent iron ions, the method for preparing the second precursor solution includes: dissolving the second monomer, the second crosslinker and the second photoinitiator in water, and then adding the above-mentioned soluble trivalent iron salt such as ferric nitrate.
[0133] It should be noted that in the embodiments of the present application, the step of preparing the first precursor solution is before step S101, and the step of preparing the second precursor solution may be before step S101 or between step S101 and step S102, and when the steps of preparing the first precursor solution and the second precursor solution are both before step S101, the order of the steps of preparing the first precursor solution and the steps of preparing the second precursor solution is not limited.
[0134] In addition, it should be noted that in the embodiments of the present application, when it is necessary to introduce trivalent iron ions, on the one hand, trivalent iron ions can be introduced into the first layer of network hydrogel, but it is not possible to introduce trivalent iron ions only into the first layer of network hydrogel without introducing trivalent iron ions into the second network hydrogel. When trivalent iron ions are introduced into the first layer of network hydrogel, the effect of trivalent iron ions will act on both the first layer of network hydrogel and the second layer of network hydrogel. Specifically, trivalent iron is added to the first layer of network hydrogel, even if the trivalent iron of the ppm level will always exist in the hydrogel, although the trivalent iron will become divalent iron after the polymerization reaction is completed, but in the first swelling of step S102 (as mentioned above, the first swelling process is carried out in the air), it will soon be oxidized to trivalent iron again by oxygen in the air, and then play a role in the second layer of network hydrogel. On the other hand, as mentioned above, trivalent iron ions can be introduced into the first layer of network hydrogel alone. When introducing trivalent ferrous ions into both the first layer of network hydrogel and the second layer of network hydrogel at the same time, it is necessary to add trivalent ferrous ions into the first precursor solution. The specific material selection and concentration of the trivalent ferrous ions are the same as the case of adding trivalent ferrous ions into the second precursor solution, and will not be repeated here.
[0135] The method for preparing the super-slippery double-network hydrogel based on the inhibitory effect in the embodiment of the present application can at least bring the following beneficial effects:
[0136] 1. In the process of preparing the hydrogel, a mold that has at least partial isolation from oxygen is used and ultraviolet irradiation is performed twice. The inhibitory effect of oxygen can reduce the friction coefficient of the hydrogel and improve the lubrication performance of the hydrogel.
[0137] 2. Introducing the inhibitor trivalent iron ions into the second hydrogel to make it participate in the polymerization reaction of the hydrogel and act on the free radicals generated by the second initiator. At the same time, using the first mold with oxygen isolation function and the second mold with at least partial oxygen isolation function can achieve a better inhibition effect, thereby significantly reducing the friction coefficient of the hydrogel to a minimum of 0.00383. Even after 6 hours of continuous friction, the friction coefficient of the hydrogel is still maintained at 0.0072.
[0138] The super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application is prepared by the preparation method of the super-slippery double network hydrogel based on the inhibitory effect of the embodiment of the present application.
[0139] In some embodiments, the super-slippery double-network hydrogel based on the inhibitory effect of the embodiments of the present application includes a first layer of network hydrogel and a second layer of network hydrogel, and the second layer of network hydrogel is coated on at least a portion of the outer layer of the first layer of network hydrogel.
[0140] In some embodiments, the friction coefficient of the super-slippery double network hydrogel based on the inhibition effect of the embodiments of the present application is 0.00383-0.01 (see the best embodiment 3 below).
[0141] The super-slippery double-network hydrogel based on the inhibitory effect of the embodiment of the present application can be widely used in the fields of cartilage repair, soft robotics, medical device surface lubrication, etc. to reduce the friction coefficient and improve the lubrication effect.
[0142] Certain features of the present technology are further illustrated in the following non-limiting examples.
[0143] 1. Examples and Comparative Examples
[0144] In the following embodiments and comparative examples, the first mold and the second mold are as follows Figure 3 A mold of the structure shown.
[0145] Example 1 (Glass-Glass-Gel)
[0146] The method for preparing the super-slippery double-network hydrogel based on the inhibitory effect of this embodiment comprises the following steps:
[0147] (1) Preparation of the first precursor solution: acrylamide (AAm) and 2-acrylamide-2-methylpropanesulfonic acid (AMPS) were dissolved in ultrapure water, and then a crosslinker N,N'-methylenebisacrylamide (MBAA) and a photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) were added and mixed to obtain a first precursor solution.
[0148] Among them, based on the total mass of the first precursor solution, in the first precursor solution: the mass fraction of acrylamide (AAm) is 1.2%, the mass fraction of 2-acrylamide-2-methylpropanesulfonic acid (AMPS) is 17%, the mass fraction of the first cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.6%, and the mass fraction of the first photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%.
[0149] (2) Preparation of the first layer of network hydrogel: The first precursor solution obtained in step (1) is placed in a first mold and irradiated under 365 nm ultraviolet light for 3 h to obtain a first layer of network hydrogel.
[0150] The first mold is a glass mold (ie, the material of the first mold is glass).
[0151] (3) Preparation of a second precursor solution: a second monomer acrylic acid, a second crosslinking agent N,N'-methylenebisacrylamide (MBAA) and a second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) were dissolved in ultrapure water to obtain a second precursor solution.
[0152] Among them, based on the total mass of the second precursor solution, in the second precursor solution: the mass fraction of the second monomer acrylic acid is 12%, the mass fraction of the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.1%, and the mass fraction of the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%.
[0153] (4) Preparation of the second layer of network hydrogel: The first layer of network hydrogel obtained in step (2) is placed in the second precursor solution obtained in step (3) and soaked for 48 hours to fully swell the first layer of network hydrogel to obtain an intermediate. The intermediate is placed in a second mold, irradiated under 365nm ultraviolet light for 3 hours, and then fully swelled in pure water for 48 hours, and the pure water is replaced every 12 hours, and the unreacted monomers are removed to obtain the second layer of network hydrogel (that is, the ultra-smooth double network hydrogel based on the inhibition effect of this embodiment, marked as Glass-Glass-Gel).
[0154] The second mold is a glass mold (ie, the material of the second mold is glass).
[0155] Example 2
[0156] This embodiment is basically the same as Embodiment 1, except that:
[0157] The preparation method of the second precursor solution in step (3) is as follows: dissolving the second monomer acrylic acid, the second crosslinking agent N,N'-methylenebisacrylamide (MBAA) and the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) in water, and then adding ferric nitrate to obtain a second precursor solution.
[0158] Among them, based on the total mass of the second precursor solution, in the second precursor solution: the mass fraction of the second monomer acrylic acid is 12%, the mass fraction of the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.1%, and the mass fraction of the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%.
[0159] In the second precursor solution, the molar concentration of trivalent iron ions is 0.15 mM.
[0160] The super-slippery double network hydrogel based on the inhibitory effect prepared in this example is labeled as DN-Hydrogel-0.15Fe 3+ .
[0161] Example 3
[0162] This embodiment is basically the same as Embodiment 2, except that:
[0163] In step (3), the molar concentration of trivalent iron ions in the second precursor solution is 0.3 mM.
[0164] The super-slippery double network hydrogel based on the inhibitory effect prepared in this example is labeled as DN-Hydrogel-0.3Fe 3 + .
[0165] Example 4
[0166] This embodiment is basically the same as Embodiment 2, except that:
[0167] In step (3), the molar concentration of trivalent iron ions in the second precursor solution is 0.45 mM.
[0168] The super-slippery double network hydrogel based on the inhibitory effect prepared in this example is labeled as DN-Hydrogel-0.45Fe 3+ .
[0169] Example 5
[0170] This embodiment is basically the same as Embodiment 2, except that:
[0171] In step (3), the molar concentration of trivalent iron ions in the second precursor solution is 0.6 mM.
[0172] The super-slippery double network hydrogel based on the inhibitory effect prepared in this example is labeled as DN-Hydrogel-0.6Fe 3 + .
[0173] Example 6
[0174] This embodiment is basically the same as Embodiment 2, except that:
[0175] In step (3), the molar concentration of trivalent iron ions in the second precursor solution is 0.75 mM.
[0176] The super-slippery double network hydrogel based on the inhibitory effect prepared in this example is labeled as DN-Hydrogel-0.75Fe 3+ .
[0177] Example 7
[0178] This embodiment is basically the same as Embodiment 2, except that:
[0179] In step (3), the molar concentration of trivalent iron ions in the second precursor solution is 0.9 mM.
[0180] The super-slippery double network hydrogel based on the inhibitory effect prepared in this example is labeled as DN-Hydrogel-0.9Fe 3 + .
[0181] Example 8 (Glass-PMMA-Gel)
[0182] This embodiment is basically the same as Embodiment 1, except that:
[0183] In step (2), the first mold is a glass mold (ie, the material of the first mold is glass); in step (4), the second mold is a polymethyl methacrylate (PMMA) mold (ie, the material of the second mold is PMMA).
[0184] The super-slippery double-network hydrogel based on the inhibitory effect prepared in this example is labeled as Glass-PMMA-Gel.
[0185] Example 9 (PMMA-PMMA-Gel)
[0186] This embodiment is basically the same as Embodiment 1, except that:
[0187] In step (2), the first mold is a polymethyl methacrylate (PMMA) mold (ie, the material of the first mold is PMMA); in step (4), the second mold is a polymethyl methacrylate (PMMA) mold (ie, the material of the second mold is PMMA).
[0188] The super-slippery double-network hydrogel based on the inhibitory effect prepared in this example is labeled as PMMA-PMMA-Gel.
[0189] Example 10 (PMMA-Glass-Gel)
[0190] This embodiment is basically the same as Embodiment 1, except that:
[0191] In step (2), the first mold is a polymethyl methacrylate (PMMA) mold (ie, the material of the first mold is PMMA); in step (4), the second mold is a glass mold (ie, the material of the second mold is glass).
[0192] The super-slippery double-network hydrogel based on the inhibitory effect prepared in this example is labeled as PMMA-Glass-Gel.
[0193] Comparative Example 1
[0194] This comparative example is basically the same as Example 1, except that:
[0195] There is no need for step (3), that is, there is no need to prepare a second precursor solution.
[0196] Step (4) is: fully swelling in pure water for 48 hours, and replacing the pure water every 12 hours to remove the unreacted monomers to obtain the final first layer of network hydrogel.
[0197] The hydrogel prepared in this comparative example is named Glass-Gel.
[0198] Comparative Example 2
[0199] This comparative example is substantially the same as Example 9, except that:
[0200] There is no need for step (3), that is, there is no need to prepare a second precursor solution.
[0201] Step (4) is: fully swelling in pure water for 48 hours, and replacing the pure water every 12 hours to remove the unreacted monomers to obtain the final first layer of network hydrogel.
[0202] The double network hydrogel prepared in this comparative example is marked as PMMA-Gel.
[0203] 2. Friction experiment of hydrogel
[0204] First, the friction coefficients of the four hydrogels of Example 1, Example 8-10 based on the oxygen inhibition effect were tested. The experimental results are shown in Figure 4 As shown. Figure 4 It can be seen that the change of the material of the first mold and the second mold will significantly affect the friction coefficient of the hydrogel. The difference in the friction coefficient of the hydrogel obtained by combining the first mold and the second mold with different materials can reach an order of magnitude, which fully demonstrates that the inhibitory effect of oxygen can effectively reduce the friction coefficient of the double network hydrogel. In addition, since the networks of the double network hydrogel have different mesh structures and chain lengths, from the perspective of reducing the friction coefficient, the inhibitory effect on different networks is not always positive. Figure 4 It can be found that Glass-PMMA-Gel (the hydrogel prepared in Example 8) has the lowest friction coefficient.
[0205] In order to further explore the potential of the inhibitory effect to reduce the friction coefficient, this application selected a highly efficient inhibitor Fe 3+ Based on the experimental results of oxygen inhibition effect, we chose to add different concentrations of trivalent iron ions only in the second layer of network hydrogel to achieve the optimal effect of reducing friction coefficient.
[0206] In order to verify that extremely small amounts of trivalent iron ions can produce significant inhibitory effects, we conducted the following experiments ( Figure 5 ):
[0207] Four second precursor solutions with different concentrations of trivalent iron ions were prepared, which were marked as second precursor solution 1, second precursor solution 2, second precursor solution 3, and second precursor solution 4, respectively. Their preparation methods were as follows:
[0208] The preparation method of the second precursor solution 1 is as follows: dissolving the second monomer acrylic acid, the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) and the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) in water, and then adding ferric nitrate to obtain the second precursor solution 1. Wherein, based on the total mass of the second precursor solution 1, in the second precursor solution: the mass fraction of the second monomer acrylic acid is 12%, the mass fraction of the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.1%, and the mass fraction of the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%; in the second precursor solution 1, the molar concentration of trivalent iron ions is 0mM.
[0209] The preparation method of the second precursor solution 2 is as follows: dissolving the second monomer acrylic acid, the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) and the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) in water, and then adding ferric nitrate to obtain the second precursor solution 1. Wherein, based on the total mass of the second precursor solution 2, in the second precursor solution: the mass fraction of the second monomer acrylic acid is 12%, the mass fraction of the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.1%, and the mass fraction of the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%; in the second precursor solution 2, the molar concentration of trivalent iron ions is 1mM.
[0210] The preparation method of the second precursor solution 3 is as follows: dissolving the second monomer acrylic acid, the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) and the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) in water, and then adding ferric nitrate to obtain the second precursor solution 1. Wherein, based on the total mass of the second precursor solution 3, in the second precursor solution: the mass fraction of the second monomer acrylic acid is 12%, the mass fraction of the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.1%, and the mass fraction of the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%; in the second precursor solution 3, the molar concentration of trivalent iron ions is 2mM.
[0211] The preparation method of the second precursor solution 4 is as follows: dissolving the second monomer acrylic acid, the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) and the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) in water, and then adding ferric nitrate to obtain the second precursor solution 1. Wherein, based on the total mass of the second precursor solution 4, in the second precursor solution: the mass fraction of the second monomer acrylic acid is 12%, the mass fraction of the second cross-linking agent N,N'-methylenebisacrylamide (MBAA) is 0.1%, and the mass fraction of the second photoinitiator phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) is 0.02%; in the second precursor solution 4, the molar concentration of trivalent iron ions is 3mM.
[0212] The second precursor solution 1, the second precursor solution 2, the second precursor solution 3, and the second precursor solution 4 were irradiated at 365nm ultraviolet light for different time periods: each second precursor solution was irradiated for 2min, 4min, 6min, and 8min, respectively, and the changes in the polymerization state of the hydrogel were observed. The results are as follows: Figure 5 As shown. Figure 5It can be seen that with the increase of the concentration of trivalent iron ions, the time required for the hydrogel to polymerize from a liquid state to a solid state hydrogel continues to increase, from the initial 2 minutes to 8 minutes. This experimental result fully demonstrates that trivalent iron ions can significantly inhibit the polymerization of hydrogels.
[0213] Based on this experiment, we tested the friction coefficients of the hydrogels of Examples 1-7 with different ferric iron concentrations. The test method was as follows: under a load of 1N, the friction coefficients of the hydrogels prepared in Examples 1-7 with different ferric iron concentrations were tested respectively. The test results are shown in FIG. Figure 6 shown.
[0214] from Figure 6 It can be seen that with the increase of the concentration of trivalent iron ions, the friction coefficient of the hydrogel experienced a process of first decreasing and then increasing. From the perspective of reducing the friction coefficient, the optimal trivalent iron concentration is 0.3mmol / L. The reason why the friction coefficient of the hydrogel experiences a decreasing and increasing section is that in addition to the inhibitory effect that can reduce the friction coefficient, the trivalent iron ions can also form weak physical crosslinks with the carboxyl groups in the second layer of network hydrogel through electrostatic action. Excessive trivalent iron ions will greatly increase the physical crosslinking, densify the hydrogel grid, and then increase the friction coefficient. This experiment proves our prediction that trivalent iron ions can reduce the friction coefficient, and explains that the inhibitory effect can effectively reduce the friction coefficient of the hydrogel. At the same time, it also determines that the optimal trivalent iron ion concentration is 0.3mmol / L, and the lowest friction coefficient is 0.00383.
[0215] Based on the above experimental results, the present invention tested the DN-Hydrogel-0.3Fe prepared in Example 3. 3+ The more detailed friction performance of the hydrogel is tested by: the sliding speed is 1mm / s, and the change of the friction coefficient of the hydrogel is observed when the load increases from 1N to 8N ( Figure 7 a) and the change in friction coefficient at a load of 1N and a sliding speed of 1mm / s for 6 hours ( Figure 7 b) Test results such as Figure 7 shown.
[0216] The PMMA-Glass-Gel hydrogel prepared in Example 10, the Glass-PMMA-Gel hydrogel prepared in Example 8, and the DN-Hydrogel-0.3Fe prepared in Example 3 were selected. 3+ The hydrogels are compared because PMMA-Glass-Gel and Glass-PMMA-Gel represent the two hydrogels with the worst and best oxygen inhibition effects, respectively, symbolizing the upper and lower limits of the inhibition effect of hydrogels. Figure 7It can be seen that as the load increases, although the difference in friction coefficients of the three hydrogels becomes smaller, DN-Hydrogel-0.3Fe 3+ It still has the lowest friction coefficient, which shows that the contribution of trivalent iron ions as an efficient inhibitor to reduce the friction coefficient ( Figure 7 a). As the friction time increases, the difference in friction performance will continue to increase, and the initially lower friction coefficient will perform better in the long-term friction test ( Figure 7 b), after 3 hours of continuous friction, only DN-Hydrogel-0.3Fe 3+ The super-slip performance (friction coefficient < 0.01) was still maintained. In addition, even after 6 hours of continuous friction, the DN-Hydrogel-0.3Fe 3+ The friction coefficient of the hydrogel still remained at 0.0072, which was 94% lower than that of the PMMA-Glass-Gel hydrogel prepared in Example 10. These experimental results further support that the high-efficiency inhibitor trivalent iron can significantly improve the friction performance of the hydrogel, and the friction coefficient of the hydrogel of the present application is very excellent in both absolute and relative values.
[0217] This experiment further tested the variation trend of friction coefficient with speed in Comparative Example 1 and Comparative Example 2, such as Figure 8 As shown, the load used in the friction test is 1N. Figure 8 It can be seen that the friction coefficient of PMMA-Gel in Comparative Example 2 is lower than that of Glass-Gel in Comparative Example 1. This is because PMMA-Gel will be affected by the inhibitory effect during the synthesis process to form a relatively loose network structure, which is consistent with the previous theory. However, the absolute value of the friction coefficient of the comparative example is basically greater than 0.01. This result is very poor compared to the best Example 3 (the friction coefficient of Example 3 is reduced by approximately 80% and 60% relative to Comparative Example 1 and Comparative Example 2, respectively). This also illustrates the advantage of choosing a double network hydrogel: under the action of the inhibitory effect, the double network hydrogel can achieve more excellent friction performance. At the same time, combined with Figure 8 and Figure 4 By comparing comparative example 1 and example 1, it is found that the friction coefficient of example 1 is reduced more, indicating that when containing a second layer of network hydrogel and both the first mold and the second mold are glass molds, the second layer of network hydrogel has a good effect on reducing the friction coefficient; by comparing comparative example 2 and example 9, it is found that the friction coefficient of example 9 is reduced less, indicating that when containing a second layer of network hydrogel and both the first mold and the second mold are PMMA molds, the second layer of network hydrogel is also helpful in reducing the friction coefficient, but the ability to reduce the friction coefficient is reduced.
[0218] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0219] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A method for preparing a super-slippery double-network hydrogel based on an inhibitory effect, characterized in that: include: subjecting the first precursor solution to a first ultraviolet irradiation in a first mold to obtain a first layer of network hydrogel; Performing a first swelling of the first layer of network hydrogel in a second precursor solution to obtain an intermediate; The intermediate is subjected to a second ultraviolet irradiation in a second mold to obtain a second layer of network hydrogel; The first mold and the second mold are molds with at least a partial oxygen isolation function; the first precursor solution includes a first monomer, a first crosslinking agent, and a first photoinitiator, and the second precursor solution includes a second monomer, a second crosslinking agent, and a second photoinitiator; the first monomer includes at least one of acrylamide, 2-acrylamide-2-methylpropane sulfonic acid, methacrylamide, sodium acrylate, and 2-hydroxyethyl methacrylate; the second monomer includes at least one of acrylic acid and methacrylic acid; The second precursor solution or the second precursor solution and the first precursor solution contain trivalent iron ions; The concentration of the trivalent iron ions in the second precursor solution or the second precursor solution and the first precursor solution is 0.15-0.6 mmol / L; the concentration of the trivalent iron ions is at the same order of magnitude as the concentration of the second photoinitiator; The material of the first mold is glass, and the material of the second mold is at least one of glass, polymethyl methacrylate, polystyrene, and polycarbonate.
2. The preparation method according to claim 1, characterized in that: The first mold is made of glass, and the second mold is made of polymethyl methacrylate.
3. The preparation method according to claim 1, characterized in that: The first cross-linking agent and the second cross-linking agent both include at least one of N,N'-methylenebisacrylamide and ethylene glycol dimethacrylate; and / or, the first photoinitiator and the second photoinitiator both include at least one of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate and photoinitiator 2959; And / or, the mass ratio of the first monomer, the first cross-linking agent, and the first photoinitiator is (15-22): (0.1-1): (0.01-0.03); And / or, the mass ratio of the second monomer, the second cross-linking agent, and the second photoinitiator is (10-14): (0.05-0.2): (0.01-0.03).
4. The preparation method according to claim 1, characterized in that: In the first ultraviolet irradiation and the second ultraviolet irradiation, the wavelength of the ultraviolet rays is 350-370nm, and the time of ultraviolet irradiation is 1-5h; And / or, the method for preparing the super-slippery double-network hydrogel based on the inhibitory effect further comprises the step of subjecting the intermediate product obtained after the second ultraviolet irradiation to a second swelling in pure water; And / or, the first swelling time is 40-56h.
5. The preparation method according to claim 4, characterized in that: The second swelling time is 40-56h; And / or, during the second swelling process of the intermediate product obtained after the second ultraviolet irradiation in pure water, the pure water is replaced every 10-12 hours.
6. A super-slippery double network hydrogel based on an inhibitory effect, characterized in that: The method is prepared according to any one of claims 1 to 5.
7. The super-slippery double network hydrogel based on the inhibitory effect according to claim 6, characterized in that: The super-slippery double-network hydrogel based on the inhibitory effect comprises the first layer of network hydrogel and the second layer of network hydrogel, wherein the second layer of network hydrogel is coated on at least a part of the outer surface of the first layer of network hydrogel.
8. The super-slippery double network hydrogel based on the inhibitory effect according to claim 6, characterized in that: The friction coefficient of the super-slippery double-network hydrogel based on the inhibition effect is 0.00383-0.
01.
9. Application of the super-slippery double-network hydrogel based on the inhibitory effect as described in any one of claims 6 to 8 in the field of soft robots, the field of medical device surface lubrication, or as a material in the field of cartilage repair.
Citation Information
Patent Citations
A method for preparing a lipid-lubricated hydrogel
CN115569235B
Lasting lubrication hydrogel and preparation method thereof
CN116854940A
Preparation method of double-network hydrogel
CN101608006A
Hydrogel and method for producing it
JP2009270032A
Artificial Meniscus
US20080119930A1